Retrospect hospital project development from briefing to completion: Case study of IIUM Teaching Hospital experiences - Mohd Nawawi, Norwina; Sapian, Abdul Razak; Zulkifly, Ahmad Hafiz (2017)
The strategic planning of International Islamic University Malaysia (IIUM) promotes the establishment of a teaching hospital for the clinical and practice of medicine. The journey towards the fruition of the hospital from before 2009 to 2016 (7 years) has been a learning path for both experienced and non-experience d professionals on the job. Being the 2nd purpose built teaching hospital after University of Malaya Medical Centre (UMMC) in Malaysia, the project has no precedent. The government decides that IIUM Hospital is to be procured through Public Private Partnership (PPP) mode and built on the basis of Shariah Compliant construction. IIUM established as a company thus tendered the hospital as “private healthcare facility” and therefore require to comply to Healthcare Facilities and Services Act 1998 were among the predicament for this project. This presentation intent to provide, very briefly, lessons learns from the inception of the project , through the formulation of the brief, the negotiation with the governing bodies, through the design development, construction and commissioning with the concessionaire, as a complete cycle. Qualitatively, as part of the User-client team, through hands-on-experience and available documentations on the job , the presentation informed steps taken at each stage with the rationale to learn or unlearn from the decisions made in an open discussion. With the limitation of time as well as inflicted with confidential material , although the hospital is yet to be fully operational, knowledge gained from this simple transaction of discussion is never too early to be shared and improved for the better.